Answer:
Step-by-step explanation:
Given the system of equation,
y = [tex]\frac{2x}{3}+2[/tex]...(1)
6x – 4y = –10 ...(2)
Substituting equation 1 into 2 we have;
6x - 4(2x/3 +2)= -10
6x -8x/3 -8 = -10
Multiplying through by 3;
18x-8x-24=-30
10x=-30+24
10x = -6
Dividing both sides by 10
10x/10 = -6/10
x = -0.6
Substituting x = -0.6 into equation 1 to get the value of y we have;
y = 2(-0.6)/3 + 2
y = -1.2/3 + 2
y = -0.4+2
y = 1.6
This shows that the linear equation has only one solution. The solution is
x = -0.6 and y = 1.6